2006
DOI: 10.1111/j.1600-0528.2006.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life and periodontal status

Abstract: This study demonstrates a significant association between oral health-related QoL and periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

53
281
8
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(356 citation statements)
references
References 38 publications
(51 reference statements)
53
281
8
14
Order By: Relevance
“…Previous studies have demonstrated that poor oral health status had negative impacts on HRQoL (Naito et al, 2010; Ng & Leung, 2006; Sandberg & Wikblad, 2003; Zhou et al, 2011), and findings from the current study agree with these results. People with periodontitis are at increased risk of oral pain and tooth loss, which leads to limited oral function such as eating, swallowing, and speaking (Furuta & Yamashita, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have demonstrated that poor oral health status had negative impacts on HRQoL (Naito et al, 2010; Ng & Leung, 2006; Sandberg & Wikblad, 2003; Zhou et al, 2011), and findings from the current study agree with these results. People with periodontitis are at increased risk of oral pain and tooth loss, which leads to limited oral function such as eating, swallowing, and speaking (Furuta & Yamashita, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported that oral diseases were significantly associated with health‐related quality of life (HRQoL) among patients attending private dental offices (Naito et al, 2010), community‐based older individuals (Wang, Chou, & Yu, 2013; Ng & Leung, 2006), or individuals with diseases related to oral health, such as diabetes (Sandberg & Wikblad, 2003) and chronic obstructive pulmonary disease (Zhou, Wang, Song, Zhang, & Wang, 2011). However, the impact of periodontitis on general HRQoL among dialysis patients has not yet been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Health-related QoL measures, including objective and subjective assessments, are especially useful for evaluating efforts to prevent disabling chronic diseases and assessing their effectiveness [12]. Assessing the consequences of impaired oral health from the patient's perspective has emerged as an important research area [13].…”
Section: Discussionmentioning
confidence: 99%
“…The significant correlation between disease severity and physical pain (P value .004 18 . The severity of periodontal disease in this current study was not significantly correlated with functional limitation.…”
Section: Oral Hygiene and Periodontal Status:-mentioning
confidence: 99%